Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 7 - 7.1 - Using Fundamental Identities - 7.1 Exercises - Page 513: 26



Work Step by Step

Remember that: $sec^2x=tan^2x+1$ $sec^2x-tan^2x=1$ $sec^4x-tan^4x=(sec^2x)^2-(tan^2x)^2=(sec^2x+tan^2x)(sec^2x-tan^2x)=(sec^2x+tan^2x)(1)=sec^2x+tan^2x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.